Assessment of mortality-related risk factors and effective antimicrobial regimens for treatment of bloodstream infections caused by carbapenem-resistant Pseudomonas aeruginosa in patients with hematological diseases - Zhen, Sisi; Zhao, Yuanqi; Chen, Zhangjie; Zhang, Tingting; Wang, Jieru; Jiang, Erlie; Zhang, Fengkui; Mi, Yingchang; Zhu, Xiaofan; Han, Mingzhe; Xiao, Zhijian; Wang, Jianxiang; et al. (Frontiers in Cellular and Infection Microbiology, 2023)
Background Infections caused by carbapenem-resistant Pseudomonas aeruginosa (CRPA) are related to higher mortality. The objective of this study was to explore clinical outcomes of CRPA bacteremia, identify risk factors and also, compare the efficacy of traditional and novel antibiotic regimens. Methods This retrospective study was conducted at a blood diseases hospital in China. The study included hematological patients who were diagnosed with CRPA bacteremia between January 2014 and August 2022. The primary endpoint was all-cause mortality at day 30. Secondary endpoints included 7-day and 30-day clinical cure. Multivariable Cox regression analysis was employed to identify mortality-related risk factors. Results 100 patients infected with CRPA bacteremia were included and 29 patients accepted allogenic-hematopoietic stem cell transplantation. 24 received ceftazidime-avibactam (CAZ-AVI)-based therapy and 76 received other traditional antibiotics. 30-day mortality was 21.0%. Multivariable cox regression analysis showed neutropenia >7 days after bloodstream infections (BSI) (P=0.030, HR: 4.068, 95%CI: 1.146~14.434), higher Pitt bacteremia score (P<0.001, HR:1.824, 95%CI: 1.322~2.517), higher Charlson comorbidity index (P=0.01, HR: 1.613, 95%CI: 1.124~2.315) and bacteremia due to multidrug-resistant Pseudomonas aeruginosa (MDR-PA) (P=0.024, HR:3.086, 95%CI: 1.163~8.197) were identified as independent risk factors of 30-day mortality. After controlling for confounders, an additional multivariable cox regression analysis revealed definitive regimens containing CAZ-AVI were associated with lower mortality in CRPA bacteremia (P=0.016, HR: 0.150, 95%CI: 0.032~0.702), as well as in MDR-PA bacteremia (P=0.019, HR: 0.119, 95%CI: 0.020~0.709). Conclusions For patients with hematological diseases and CRPA bacteremia, 30-day mortality rate was 21.0% (21/100). Neutropenia >7 days after BSI, higher Pitt bacteremia score, higher Charlson comorbidity index and bacteremia due to MDR-PA increased 30-day mortality. CAZ-AVI-based regimens were effective alternatives for bacteremia due to CRPA or MDR-PA.